2001
DOI: 10.1002/1522-2683(200108)22:13<2701::aid-elps2701>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Robust and cost-effective capillary electrophoresis-mass spectrometry interfaces suitable for combination with on-line analyte preconcentration

Abstract: This paper describes several successful cost-effective attempts to couple capillary electrophoresis (CE) and mass spectrometry (MS) without make-up flow or nebulizing gas. An in-depth analysis of several interfaces using conductive spray tips was performed as well as an easy-to-prepare T-junction with direct electrode contact, the latter being the most robust interface. No coating is necessary and the spray voltage is applied through a gold wire positioned at the gap between the separation and spray capillarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…A means to close the CE electrical circuit for analyte separation while simultaneously providing an electrical potential to the spray tip is necessary. The common interfaces can be divided into three categories: sheath-flow 16,[18][19][20]24,27,32,37,38,40,43,47,50,[53][54][55][56]60,66 and sheathless 15,17,25,26,[28][29][30]34,36,44,45,48,49,61 and liquid-junction interfaces. [92][93][94] In the sheath-flow design, a coaxial sheath liquid, usually a hydroorganic mixture, mixes with the capillary eluent at the outlet end of the capillary.…”
Section: ·1 Esi-msmentioning
confidence: 99%
See 2 more Smart Citations
“…A means to close the CE electrical circuit for analyte separation while simultaneously providing an electrical potential to the spray tip is necessary. The common interfaces can be divided into three categories: sheath-flow 16,[18][19][20]24,27,32,37,38,40,43,47,50,[53][54][55][56]60,66 and sheathless 15,17,25,26,[28][29][30]34,36,44,45,48,49,61 and liquid-junction interfaces. [92][93][94] In the sheath-flow design, a coaxial sheath liquid, usually a hydroorganic mixture, mixes with the capillary eluent at the outlet end of the capillary.…”
Section: ·1 Esi-msmentioning
confidence: 99%
“…100 Chang and Her 15 carbon-coated the tapered capillary outlet using a soft pencil, while McComb and Perreault 17 used gold. Waterval et al 29 compared gold and silverpaint-coated conductive spray tips, and reported an easyto-prepare T-junction for direct electrode contact, prepared by positioning a gold wire at the gap between the separation capillary and a pulled capillary tip connected by a small transparent rubber. Wetterhall et al 34 used a conductive polypropylene/graphite mixture for the production of polymeric nanospray needle emitters.…”
Section: ·1 Esi-msmentioning
confidence: 99%
See 1 more Smart Citation
“…These chromatographic mechanisms can be of low specificity or of high specificity. Basically, three methods are available using a low-specific chromatographic mechanism: (i) solid adsorptive phase chromatography, including solid-phase extraction (SPE) and membrane preconcentration (mPC) [2,[16][17][18][19][20][21][22][23][24], (ii) liquid distribution phase chromatography, including electroextraction (EE) [2] and supported liquid membranes (SLM) [25,26], and (iii) hollow fibers [27,28]. Low-specific chromatography is probably the most widely used application of chromatographic retention.…”
Section: Chromatography-based Preconcentrationmentioning
confidence: 99%
“…The on-capillary preconcentration has the benefit that sample loading is not limited to the capillary volume and that on-line purification of the applied sample can be accomplished by employing washing steps. The observed capacity of the adsorptive phase allows introduction of typical LC injection volumes, rather than the normally employed nL volumes of CZE [32]. Desorption of the trapped analytes can be accomplished with minimum amounts of elution solvent, compatible with the subsequent CZE separation.…”
Section: Introductionmentioning
confidence: 99%